Application of Mixed Time Partitioning Methods to Raise the Efficiency of Solidification Modeling - Gawronska, Elzbieta; Sczygiol, Norbert (2010 12th International Symposium on Symbolic and Numeric Algorithms for Scientific Computing, 2010)
In this paper we focus on the application of a mixed time partitioning methods to raise efficiency of the solidification kernel in the NuscaS system. We are proposing using a fixed time step in the casting and its integer multiple in other parts of mould because the time step size determines the accuracy of the simulation results. By means of numerical experiments we show that our approach allows for up to about three times performance improvement as compared to the standard approach without loosing precision of results. Moreover, this methods will be extended to 3D numerical simulation in a future work. We notice also that our method can be combined with parallel processing to further improve performance of solidification kernels.